PENGGUNAAN GAYA MENGAJAR INKLUSI VNTUK MENGEMBANGAN DEMOKRATISASi BELAJAR DALAM PEMBELAJARAN PENDIDIKAN JASMANI DI SEKOlAH DASAR - Agus Suryobroto (Jurnal Cakrawala Pendidikan, 2001)
Den10crati=afio/] (~f' learniJlg is not )Jel significulltly actualized in the teachinglearningprocess 0.1' pJlysical educatiol1 at elelnell(ary selzo()l de~pite its considerableil11portance in educating learners to practice de1110Cracy. In essence democratization can betaught via classes oj' physical education at elemelltary .\·cll001 thr()ug/z to those at theulliversily level. In tIle pre..,·en( erll {~f' re.f()rnlation, denl()Crati=ati()11 L,' greatly needed by allJl1eJnbers 0.(society in living as a state and a nation.Tlze inclusion leae/zing style is one 0.1' tlze teaelzifzg styles in teaching physicaleducation whic/1 can give learners illus(rali()n~,' (if 11()W I() dem()crati=e. Tile anatolny oftheinclusion teaching f)f(yle consL.,,'ls (if tIle leacller making decisions be.fiJre class sessions, thelearners Inaking decisions in cla..\s ..\'essions, alld tlze learners Inaking decisions after classsessions.To acfuali=e education in democruc..y ill. clas..\'e..'" ojjJJzy..\'ical educatioll, the inclusionleae/zing style can be applied ()11 suell classes at elenlelltary school tllr()uglz to tllose at tIleuniversity level.